Aspek Hukum Pidana Perampasan Jenazah Akibat Covid-19 Menurut Undang-Undang Nomor 6 Tahun 2018 Tentang Kekarantinaan Kesehatan - Pattinama, Kevin Gilbert; Pasalbessy, John Dirk; Latupeirissa, Julianus Edwin (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The community plays an important role in complying with Government regulations and policies in suppressing the chain of transmission of Covid-19, for example, wearing masks, maintaining cleanliness, washing hands, and so on.Purposes of the Research: The purpose of this study is to provide an overview of the qualifications of the crime of taking the corpse of Covid-19 according to the statutory regulations and the obstacles to investigating the crime of taking the body of Covid-19.Methods of the Research: Research methods are used with normative juridical research types. The problem approach used is the legal approach, concept analysis approach, case approach, Source of legal materials used primary legal materials and secondary legal materials. Collection techniques through literature studies and then analyzed through the way of description using qualitative methods. Result of the Research: The results of this study show that a criminal act of confiscating a corpse due to Covid-19 was committed by unscrupulous residents of Batu Merah Village, Ambon City. In the Judge's decision, the defendants had fulfilled the criminal element, namely the existence of actions from everyone who did not comply with the implementation and/or obstructed the implementation so that it caused a Public Health Emergency. With the higher rate of transmission of the virus, investigators are afraid to face face to face to examine suspects or witnesses. Therefore, the government needs to make specific regulations regarding the criminal act of confiscating the corpse of Covid-19.